Implementing a Web-Based Alumni Information System to Strengthen Data Governance in Secondary Education - Riska Kherani; Akbar Iskandar; Mansyur Mansyur; Nurhalisa Nurhalisa; Kumar Vivek (Yayasan Cendekiawan Digital Indonesia, 2025)
The growing demand for transparent, accurate, and participatory data governance in secondary education has exposed limitations in conventional alumni data management practices in many senior high schools, particularly those that rely on manual records or fragmented digital files. This article reports on the design and implementation of a web-based alumni data management information system developed as a community service-based applied study to support institutional efficiency and alumni engagement. The system development process was informed by a needs assessment involving school administrators and alumni, with data collected through direct observation, semi-structured interviews, and questionnaires. System functionality was evaluated using Black Box Testing to verify compliance with predefined operational requirements. The implementation involved a single senior high school as the institutional partner, with administrative users and alumni as the primary system users. Functional testing results confirmed that all core modules, authentication, alumni data management, information dissemination, and data reporting, operated as intended without critical errors. The system enabled real-time data updating and reduced administrative dependency on physical presence, indicating improved operational efficiency and data accessibility. From a broader perspective, this study contributed a replicable community-oriented model for implementing alumni information systems in secondary education, demonstrating how web-based platforms can strengthen institutional alumni interactions and support digital transformation agendas across diverse educational contexts.